Perbandingan Lama Rawat Pasien Covid-19 Dengan Komorbid Diabetes Melitus Berdasarkan Tingkat Usia Di Rumah Sakit Natar Medika Lampung Selatan - Firhat Esfandiari; Ismalia Husna; Resti Arania; Husnul Khotimah (Universitas Malahayati Lampung, 2022)
ABSTRACT Corona virus or commonly known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new virus that can infect the respiratory system of an infected person, this virus is commonly called Covid-19. Signs and symptoms of Covid-19 infection include symptoms of acute respiratory distress such as fever, cough and shortness of breath. The average incubation period is 5-6 with the longest incubation period being 14 days. In severe cases of Covid-19 it can cause pneumonia, acute respiratory syndrome, kidney failure and death. To determine the difference between the length of stay for Covid-19 patients and age-level comorbid diabetes mellitus at Natar Medika Hospital Lampung. This type of research uses a descriptive-comparative research method with a cross-sectional approach. Sampling technique in the form of Total Sampling. Respondents in this study were Covid-19 patients with comorbid diabetes mellitus at Natar Medika Hospital in 2021 as many as 41 patients. Based on the average distribution of Covid-19 patients with comorbid diabetes mellitus aged 20-60 years, there were 18 patients with an average score (25.53). Meanwhile, for Covid-19 patients with comorbid diabetes mellitus with an elderly age of 60 years, there were 23 patients with an average score (17.46) for a total of 41 patients. The results of the data analysis in this study are the comparison of the length of stay for Covid-19 patients with comorbid diabetes mellitus with an adult age level of 20-60 years and an elderly 60 years with a value (p-value 0.017) meaning Ho is rejected and Ha is accepted. The results of the Mann-Whitney statistical test were obtained with the results p=0.017 (p0.05). Conclusion: There is a comparison between adults aged 20-60 years and elderly 60 years in Covid-19 patients with comorbid diabetes mellitus at Natar Medika Hospital South Lampung in 2021. Keywords: Diabetes Mellitus, Covid-19, Age ABSTRAK Corona virus atau yang biasa dikenal dengan Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) adalah virus baru yang dapat menginfeksi sistem pernapasan seseorang yang terinfeksi, virus ini biasa disebut Covid-19. Tanda dan gejala umum infeksi Covid-19 antara lain gejala gangguan pernapasan akut seperti demam, batuk dan sesak napas. Masa inkubasi rata-rata 5-6 hari dengan masa inkubasi terpanjang 14 hari. Pada kasus Covid-19 yang berat dapat menyebabkan pneumonia, sindrom pernapasan akut, gagal ginjal dan kematian. Untuk mengetahui perbedaan lama rawat pasien Covid-19 dengan komorbid diabetes melitus berdasarkan tingkat usia di Rumah Sakit Natar Medika Lampung. Jenis penelitian ini menggunakan metode penelitian deskriptif-komperatif dengan pendekatan cross – sectional. Teknik pengambilan sampel berupa Total Sampling. Responden dalam penelitian ini adalah pasien Covid-19 dengan komorbid diabetes melitus di Rumah Sakit Natar Medika tahun 2021 berjumlah 41 pasien. Diketahui distribusi rata-rata pasien Covid-19 dengan komorbid diabetes melitus berdasarkan tingkat usia dewasa 20-60 tahun terdapat 18 pasien dengan nilai rata-rata (25.53). Sedangkan untuk pasien Covid-19 dengan komorbid diabetes melitus dengan usia lansia 60 tahun terdapat 23 pasien dengan nilai rata-rata (17.46) dengan jumlah total 41 pasien. Hasil analisa data dalam penelitian ini yaitu perbandingan lama rawat pasien Covid-19 dengan komorbid diabetes melitus dengan tingkat usia dewasa 20-60 tahun dan lansia 60 tahun dengan nilai (p-value 0.017) artinya Ho ditolak dan Ha diterima. Hasil uji statistic Mann-Whitney di dapatkan dengan hasil p=0.017 (p0,05). Ada perbandingan antara usia dewasa 20-60 tahun dan lansia 60 tahun pada pasien Covid-19 dengan komorbid diabetes melitus di Rumah Sakit Natar Medika Lampung Selatan. Kata Kunci: Diabetes Melitus, Covid-19, Usia